P83 Explaining the fall in coronary mortality in argentina between 1995 and 2010: impact modelling analysis. (2nd September 2017) - Vicens, J; Perman, G; Bandosz, P; Guzman, M; Ferrante, D; Schargrodsky, H; Aliperti, V; Pramparo, P; O'Flaherty, M; Figar, S
Abstract : Background: Coronary heart disease (CHD) mortality has declined substantially in Argentina in the last decades. However, the contributory factors remain unclear because major CHD risk factor levels have paradoxically increased, notably physical inactivity, obesity and diabetes. our objectiv is to quantify the contributions of prevention and treatment to the coronary heart disease mortality trends in Argentina between 1995 and 2010. Methods: We used the previously validated IMPACT model to analyse mortality trends between 1995 and 2010 in the Argentinean population aged 25 years and over. This model integrates data on changes in population size, CHD mortality, risk factors, and uptake of evidence-based cardiac treatments. Main data sources included official vital statistics, national health surveys, and published papers in the scientific literature. If none of these were available, we used expert judgement. Relative risks and regression coefficients came from the published meta-analyses. The difference between observed and expected CHD deaths in 2010 was then partitioned among treatment benefits and risk factor changes. We also performed probabilistic sensitivity analyses to quantify the potential effects of parameter uncertainty. Results: From 1995 to 2010, age-adjusted CHD mortality rates in Argentina fell by 24.1%, resulting in 8500 fewer CHD deaths in 2010 had mortality rates remained unchanged. Improvements in medical and surgical treatments were associated with 53.8% (95% uncertainty interval, 46.2% –61.8 %) of the total mortality decrease. Major contributions came from heart failure therapies (15.1%), antihypertensive medication (11.9%), and secondary prevention following acute myocardial infraction (8.2%). Risk factor changes accounted for 40.4% (9.5% to 65.6 %) of the mortality fall. Decreases in systolic blood pressure accounted for 34.6%; in cholesterol levels, 19.9%; and in smoking prevalence, 6.7%. However, rises in diabetes, BMI and physical inactivity negated some of these benefits, potentially increasing mortality by 9.4%, 6.4% and 5.0%, respectively. Approximately, 6% of the deaths prevented or postponed could not be explained in our model. Results: Approximately 54% of the CHD mortality fall in Argentina between 1995 and 2010 was attributable to increases in evidence-based medical treatments, and 40% to falls in population risk factors. However, the substantial contributions from falls in blood pressure, cholesterol and smoking were offset by adverse trends in diabetes, obesity and physical inactivity. Our results highlight the potential for further improvements in cardiovascular